Designing Cloud-Native Intelligent Systems for Workforce Analytics and Enterprise Decision-Making - Atluri, Anusha (International Journal of AI, BigData, Computational and Management Studies, 2026)
Businesses that want to develop, get more done, make their employees healthier, and use new technology require labor analytics. Businesses may do more than simply fill out standard HR paperwork. They may also need to know about workers who are supposed to turn up and those who are already scheduled to work. Cloud computing, artificial intelligence, and the collection of more data have all become better, which is why these developments occurred. You may use the information from these tools to help you make decisions regarding hiring, performance evaluations, team building, and getting staff interested, among other things. A lot of firms still utilize outdated, rigid, and data-driven solutions to run their HR and make decisions. A lot of legacy labor analytics tools use models and data sources that don’t perform well together and can’t be used together. So, it could be challenging to acquire information in real time and cooperate with individuals from various areas. If a firm needs more complex analytics, needs to incorporate data from several sources, or has to modify how it does things, these options may not work for them. People that work in open, hybrid, or international environments will have an easier time understanding strange HR practices. This article speaks about how smart system designs and cloud-based features affect the way digital organizations employ labor analytics. You may combine global data sources, AI-powered decision support systems, and analytical tools into one framework. This is a really new and advanced way to create a system. This allows companies develop workforce intelligence systems that can manage more intricate situations while still obeying the regulations and keeping everyone safe. The main findings reveal that the proposed strategy makes it simpler to receive information, makes people think, and helps individuals make choices in varied work environments. The book may help groups plan and figure out how to bring everything together in a manner that works.